2008
DOI: 10.1029/2007gl032100
|View full text |Cite
|
Sign up to set email alerts
|

Cyclonic and anticyclonic motion in the upper ocean

Abstract: Upper ocean variability is highly energetic and contributes to key processes such as heat transport and water mass formation. Here, the distribution of ocean surface cyclonic and anticyclonic motion is computed from global drifter observations for scales from large eddies to submesoscale. Two zonal bands of small‐scale motion are recovered: a known anticyclonic band at 30°–40° latitude, mostly wind‐induced, and an unexpected cyclonic band at 10°–20° latitude. It is suggested that this is due to submesoscale pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 22 publications
1
47
1
Order By: Relevance
“…Non-zero values for the spin are associated with cyclonic (Ω>0 in Northern hemisphere) or anticyclonic (Ω<0) motions of the drifter. Large values of the spin are associated with drifter looping and spiraling; trajectories presenting such features are often referred to as loopers (Richardson, 1993, Griffa et al, 2008. When the drifter is in the core of a coherent eddy, the spin value provides a good estimate of the relative vorticity ζ (ζ ~ 2Ω, Veneziani et al, 2005).…”
Section: The Drifter Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-zero values for the spin are associated with cyclonic (Ω>0 in Northern hemisphere) or anticyclonic (Ω<0) motions of the drifter. Large values of the spin are associated with drifter looping and spiraling; trajectories presenting such features are often referred to as loopers (Richardson, 1993, Griffa et al, 2008. When the drifter is in the core of a coherent eddy, the spin value provides a good estimate of the relative vorticity ζ (ζ ~ 2Ω, Veneziani et al, 2005).…”
Section: The Drifter Datasetmentioning
confidence: 99%
“…To do so, we calculate for each drifter trajectory the spin Ω (Borgas et al, 1997), which represents the mean rotation per time interval along the trajectory (Veneziani et al, 2004, Griffa et al, 2008:…”
Section: The Drifter Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Drifters and floats typically can extract these values regionally, from the number of loops or their vorticity sign (e.g., Trani et al 2011;Griffa et al 2008;Shoosmith et al 2005). However, it is difficult to quantify the horizontal and vertical extents of eddies with these sparse Lagrangian data.…”
Section: Eddy Thicknessmentioning
confidence: 99%
“…Iskandar et al, (2010) confirmed the direction of propagation of the eddy to the west, and further added that they are part of the Rossby waves. Other than cyclonic eddies, there are also anticyclonic eddies that spin in a counter-clockwise direction for southern hemisphere (Griffa et al, 2008). In 1959 and 1960, Wyrtki (1962) detected anticyclonic eddies near the SEC.…”
Section: Introductionmentioning
confidence: 99%